Analisis Strategi Bisnis pada Perusahaan Logistik PT Putra Rajawali Kencana Guna Mempertahankan Kesehatan Perusahaan - Fazrul, Fandy Ahmad; Kusumasari, Indah Respati (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
In every running company, having a business strategy is mandatory. In order to maintain consumers and income, companies need a business strategy and also a marketing strategy. The purpose of this research is so that students can find out how companies must maintain their health with their business strategies. This research was conducted using a descriptive qualitative method which will be explained descriptively. The company uses a strategy to maintain quality and trust in consumers to maintain their loyalty.